Digital compression of still images and video - Clarke, Roger J. (Signal processing and its applications, 1995)
Digital Compression of Still Images and Video is general in approach, and covers all the recognised coding algorithms, explaining their basic theory in enough detail to understand the principles involved, and discussing the results which have been achieved with them by research workers in all parts of the world